Architectural Ecology as a Scientific Direction in the History and Theory of Architecture (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The intersection of architecture and ecology represents a transformative paradigm within the field, serving as both a theoretical framework and a practical approach to design. As societies increasingly confront environmental challenges, the principles of architectural ecology emerge as crucial in re-evaluating historical practices while informing contemporary methodologies. By analyzing traditional structures such as the Suzhou classical gardens, which exemplify the interaction of human creativity and natural landscapes, one can discern fundamental principles that have sustained aesthetic and functional relevance through time (Xu Z et al.). Moreover, exploring the architectural and urban planning features of railway stations, such as those along the Trans-Siberian Railway, illustrates the adaptability of architectural designs to specific environmental contexts, emphasizing a need for ecologically sensitive urban development (E Glatolenkova). Thus, the study of architectural ecology provides an essential lens for understanding the evolution and future trajectory of architectural practices in response to ecological imperatives.